2020
DOI: 10.51703/bm.v2i2.18
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation Effects of Customer Satisfaction on the Relations Between Product Price, Service Quality and Purchasing Decision

Abstract: This research has two main objetives: (1) to examine the effect of price, service quality and costumer satisfaction on costumer’s purchasing decision, (2) to test the mediation effects of the costumer satisfaction on the relations between product price and service quality on purchasing decision. Data was collected from 82 insurance company’s costumers using questionnaire, and hypothesis was tested using Smart- PLS 3.0. The findings reveal that (1) price, service quality and costumer satisfaction have direct an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
1
6
0
2
Order By: Relevance
“…This is because the purchasers have to figure out the balance and the value between the price and product performance (quality of the product) that they have before buying them (Voss et al, 1998). Many studies have shown that price influence positively and significantly on the customer's purchasingdecision (Asadi et al, 2014;Papafotikas et al, 2014;Song et al, 2019;Zietsman et al, 2019;Carvalho et al, 2020;Hati et al, 2021). Therefore, hypothesis of this study will be as follow:…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the purchasers have to figure out the balance and the value between the price and product performance (quality of the product) that they have before buying them (Voss et al, 1998). Many studies have shown that price influence positively and significantly on the customer's purchasingdecision (Asadi et al, 2014;Papafotikas et al, 2014;Song et al, 2019;Zietsman et al, 2019;Carvalho et al, 2020;Hati et al, 2021). Therefore, hypothesis of this study will be as follow:…”
Section: Hypothesismentioning
confidence: 99%
“…Product price generally as preferred option for consumers to buy any products/ services from a company (Asadi et al, 2014;Hustić and Gregurec, 2015), therefore price has significant effect on product value and costumer purchasing decision (Asadi et al, 2014;Papafotikas et al, 2014;Song et al, 2019;Zietsman et al, 2019;Carvalho et al, 2020;Hati et al, 2021). However, previous empirical studies also revealed that product price does not influence significantly consumer purchasing decision (Gok et al, 2019) or adverse impacts on purchasing decision (Kukar-Kinney et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Customer satisfaction is a crucial thing that encourages consumers to buy and consume products that have been destroyed, it is known that product quality depends on customer satisfaction (Rivai, 2021). Customer satisfaction is a feeling of pleasure that can arise after reaching a product with the desired performance (de Fatima Carvalho et al, 2020). Customers will be reluctant to buy if they judge the product's price as not commensurate with the benefits obtained.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Price is part of the marketing mix which is considered as a tool to increase profitability and customer satisfaction. The impact of material value, service quality, and the relationship of consumer satisfaction on equity and purchase decisions, as evidenced by the research of Carvalho et al (2020) shows that price, service quality, and customer satisfaction strongly and directly influence purchasing decisions. From some of these studies, authors propose the following hypothesis: H2: Price has strong relevance and has a significant effect on purchasing decisions through customer satisfaction.…”
Section: Price Relationship To Customer Satisfactionmentioning
confidence: 99%
“…In contrast to the findings of Hanaysha, (2016) that the price of a product or service can affect the level of satisfaction among customers, because every time they respond to the value given to the product or service purchased, they tend to consider the price. Carvalho et al, (2020) Ultimately, this study aims to provide a thinking structure that can enhance and integrate the literature on product, price and service related purchasing decisions influenced by customer satisfaction in the banking sector.…”
Section: Introductionmentioning
confidence: 99%